1996
DOI: 10.1007/s0021663540477
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of high resolution gas chromatography with electron impact and negative ion mass spectrometry detection for the determination of coplanar polychlorobiphenyl congeners in sewage sludges

Abstract: The three most toxic coplanar PCB 77, 126 and 169 have been identified and quantified at ultra trace levels (0.02-4.8 ng/gdw) in swiss sewage sludge samples applying high resolution capillary gas chromatography (HRGC) and electron impact (EI) as well as negative ion chemical ionization (NCI) mass spectrometry (MS). NCI mass spectra have been dominated by the molecular ion as base peak and virtually no fragmentation has been observed. Detection limits of the planar PCB under single ion monitoring (SIM) conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…439 GC/EI-MS and GC/NCI-MS methods were compared for measuring PCBs in soils 439 or sewage sludge. 441 Another paper compared GC/MS to GC/ electron capture detection (ECD) and GC/AED for determining PCBs in highly contaminated marine sediments. 442 This comparison revealed that GC/MS (both low and high resolution) and GC/ECD measurements suffered from interferences from the complex matrix, whereas GC/AED in the chlorineselective mode provided good PCB profiles without interferences.…”
Section: Pahs and Pcbsmentioning
confidence: 99%
See 1 more Smart Citation
“…439 GC/EI-MS and GC/NCI-MS methods were compared for measuring PCBs in soils 439 or sewage sludge. 441 Another paper compared GC/MS to GC/ electron capture detection (ECD) and GC/AED for determining PCBs in highly contaminated marine sediments. 442 This comparison revealed that GC/MS (both low and high resolution) and GC/ECD measurements suffered from interferences from the complex matrix, whereas GC/AED in the chlorineselective mode provided good PCB profiles without interferences.…”
Section: Pahs and Pcbsmentioning
confidence: 99%
“…GC/EI-MS and GC/NCI-MS methods were compared for measuring PCBs in soils 439 or sewage sludge . Another paper compared GC/MS to GC/electron capture detection (ECD) and GC/AED for determining PCBs in highly contaminated marine sediments .…”
Section: Pahs and Pcbsmentioning
confidence: 99%
“…Also plasma is often used as matrix in many laboratories (20). The extraction of lipophilic PCBs from serum or plasma is mostly done with solvents or solvent mixtures like hexane:dichloromethane (306), hexane:diethyl ether (53), hexane (142) or acetonitrile (431). The solvent extract is often washed with acid or base to remove large quantities of organic co-extractives.…”
Section: Measurements and Analysis Of Workplace Exposurementioning
confidence: 99%
“…This ensures that subsequent commonly used column chromatography procedures are not overloaded by organic material. Adsorbent columns reported for sample purification include silica gel (20,201,431), Florisil (88,201,306,363), carbon (130), basic alumina (201), potassium silicate (431) and acid impregnated silica gel columns (431). Also liquid-lipophilic gel partitioning as the lipid extractive step without acid treatment has been reported for blood samples (290,417).…”
Section: Measurements and Analysis Of Workplace Exposurementioning
confidence: 99%